1991
DOI: 10.1093/nar/19.19.5321
|View full text |Cite
|
Sign up to set email alerts
|

Adult chcken α-globin gene expression in transfected QT6 quail cells: evidence for a negative regulatory element in the αD gene region

Abstract: The chicken adult alpha-globin genes, alpha A and alpha D, are closely linked in chromosomal DNA and are coordinately expressed in vivo in an approximate 3:1 ratio, respectively. When subcloned DNAs containing one or the other gene are stably transfected into QT6 quail fibroblasts, the alpha A-globin gene is expressed at measurable RNA levels, but the alpha D gene is not. The alpha A gene expression can be considerably increased by the presence of a linked Rous sarcoma virus long terminal repeat enhancer, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The possibility may thus be suggested that besides activation of the α D gene promoter the formation of an active chromatin hub in cells transcribing α A and α D genes is necessary for activation of the ‘adult’ sub-domain of the α-globin gene cluster. Among other molecular events necessary for this activation one may consider inactivation of the silencer element located upstream of the α D gene and active in respect of both α D and α A gene promoters (43). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility may thus be suggested that besides activation of the α D gene promoter the formation of an active chromatin hub in cells transcribing α A and α D genes is necessary for activation of the ‘adult’ sub-domain of the α-globin gene cluster. Among other molecular events necessary for this activation one may consider inactivation of the silencer element located upstream of the α D gene and active in respect of both α D and α A gene promoters (43). …”
Section: Discussionmentioning
confidence: 99%
“…However, the pattern of α-globin gene domain transcription was extensively studied in the past and no signs of such bi-cistronic pre-mRNA were detected ( 2 ). Furthermore, the promoter of the α A gene is well characterized and there are no reasons to suppose that this promoter is not active in living cells ( 8 , 42 , 43 ). A more attractive model is that the α A gene promoter is activated by the enhancer located <1 kb downstream of the end of the α A gene ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has also accumulated for the importance of negative control of transcription of genes in a wide variety of contexts (reviewed in [6][7][8][9][10][11]. In the context of erythroid-specific gene expression in particular, there have been various reports of negative regulation of globin (12)(13)(14)(15)(16)(17)(18)(19) and non-globin genes such as the histone H5 gene (20,2 1), the erythropoietin receptor gene (22) and the glycophorin B gene (23).…”
Section: Introductionmentioning
confidence: 99%